VOLUMETRIC ANALYSIS OF LYMPHOCYTE LIPID DROPLETS IN TYPE 2 DIABETES MELLITUS PATIENTS WITH HYPERLIPIDEMIA - Živković, Aleksa (Medicinski podmladak, 2023)
Introduction: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder characterized by inadequate glucose homeostasis. A common occurrence in T2DM is diabetic dyslipidemia. Given lipid droplets’ role in intracellular lipid storage, these structures lie at the center of lipid and energy homeostasis. Lipolysosomes are cell organelles that have the structure of lipid droplets surrounded by a membrane. Lipophagy is a selective form of autophagy which enables lipid droplet degradation, thus representing an important mechanism in the regulation of lipid droplet homeostasis.The Aim: The aim of our research was fractional volume analysis of lipid droplets, autophagic vesicles containing lipid droplets and lipolysosomes in the lymphocytes of patients with T2DM and hyperlipidemia. Material and Methods: Mononuclear cells were isolated from the peripheral blood of T2DM patients with hyperlipidemia and from healthy individuals. Cells were fixed in glutaraldehyde and postfixed in 1% osmium tetroxide. After contrasting with 4.7% uranyl acetate, the samples were embedded in epoxy resins and cut by an ultramicrotome. The ultrathin sections were then contrasted with uranyl acetate and lead citrate and analyzed using transmission electron microscopy. The fractional volume of lipid droplets, autophagic vesicles containing lipid droplets and lipolysosomes was determined using the double “coherent point“ grid with dots distributed at two different densities. Results: While there was no difference in the fractional volumes of lipid droplets and autophagic vesicles containing lipid droplets, the fractional volume of lipolysosomes was significantly higher in the lymphocytes of T2DM patients with hyperlipidemia compared to healthy individuals (p < 0.05). Conclusion: A higher fractional volume of lipolysosomes revealed in the lymphocytes of T2DM patients with hyperlipidemia can be due to an increase in the activity of these organelles, as well as an overall increase in cellular lipid metabolism in these patients.
Keywords: type 2 diabetes mellitus; hyperlipidemia; lipid droplets; autophagic vesicles containing lipid droplets; lipolysosomes